Hidden Curriculum Design of Traditional Art Community Rampak Kendang - Fery Setyaningrum; Heni Siswantari; Lono Lastoro Simatupang; Paramitha Dyah Fitriasari (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2019)
The hidden curriculum is defined as the hidden curriculum imposed on system-specific education (both formal and non-formal. Discussion of the curriculum in Indonesia is interesting is related to the hidden curriculum in non-formal education is the Rampak Kendang community. The characteristics of the population and the different teaching processes from other cities can form different and exciting outputs to be studied. The purpose of this study is to find and describe curriculum designs in the traditional art community of Rampak Kendang in Patimuan Cilacap, Indonesia. This study used a qualitative descriptive method. Data collection techniques using observation, interviews, and documentation. Participation observation with the subject of scrutiny and discussions with the Rampak Kendang community, Patimuan community, the Department of Education in Patimuan. Analysis of the data used data reduction, data presentation, and data verification. The results of this study are the discovery of curriculum design in the form of a hidden curriculum prototype of the Patimuan Rampak Kendang. In the prototype, there is an art learning process through agents as trainers (community leaders) equipped with Patimuan (Sundanese Javanese) art and arts (engineering creativity). This is then taught through training (learning processes) to other members of the Rampak Kendang community, in the long learning process influenced by the consensus (mutual agreement), and the support system form society. So that six more slices are found in the form of P, T, I (Process, Textual, Internal), K, P, I (contextual, Internal Process), T, P, E (Textual, Process, External), K, H, E (contextual, result, external), T, H, E (Textual, Result, External), K, I, H (Contextual, Internal, Result). These processes resulted in the discovery of the development of multiple intelligence members, namely kinesthetic, musical, visual-spatial, verbal, interpersonal, and intrapersonal.